Phonological nativisation of Malaysian English in the cartoon animation series “Upin and Ipin: the helping heroes” / Nur Fatima Wahida Mohd Nasir and Hajar Abdul Rahim - Mohd Nasir, Nur Fatima Wahida; Abdul Rahim, Hajar (Universiti Teknologi Mara Cawangan Pulau Pinang, 2021)
In Malaysia, “Upin and Ipin: The Helpling Heroes” is considered one of the most popular cartoon animations recently being previewed in its main channel on YouTube. This animation series presents several distinguishing features, including basic English as its primary instruction medium. Through much observation, however, this research discovers that subtle phonological nativisations of Malaysian English (ME) seem to be visible in the cartoon, which brings to the question of whether Malaysians can accept the learning of the English language with Malaysian English (ME) phonology. The identification and examination of phonological nativisation in the study were employed through a phonological analysis. These sounds' characteristics were then categorised into existing phonological features of ME based on previous literature. Findings of the study show that overall, a number of seven categories of ME’s phonological nativisation were identified, including; (1) voiced dental fricatives /ð/ replaced with voiced alveolar stops /d/; (2) voiceless dental fricative /θ/ replaced with voiceless alveolar stops /t/; (3) the omission of single coda consonants; (4) the omission of final consonant clusters; (5) the omission of morphological markers in final clusters; (6) the lengthening of vowels in unstressed syllables; and (7) the shortening of vowels in stressed syllables. Thus, it can be concluded that based on a large number of viewers, the identification of phonological nativisations of ME in the cartoon clearly reflects that the variety is gradually and unconsciously becoming accepted by Malaysians despite disagreements on the damages it may cause towards English language development.